The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.orgel.2012.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of soluble naphthalene diimide derivatives bearing long alkyl chains as n-type organic thin-film transistor materials

Abstract: Abstract:In this study, several naphthalene tetracarboxylic acid diimide (NTCDI) 2 derivatives substituted at the N and N' positions with long normal alkyl chains of different lengths were evaluated as soluble n-type organic thin-film transistor (TFT) materials. NTCDI derivatives with diundecyl (NTCDI-C11), didodecyl (NTCDI-C12), and ditridecyl (NTCDI-C13) exhibited acceptable solubility in chloroform, and their TFTs showed typical n-type TFT performance with relatively high field effect electron mobility (~0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 35 publications
5
36
0
Order By: Relevance
“…In previously reported NDI derivatives, introducing N ‐substituted flexible alkyl groups resulted in high solubility in common organic solvents. However, the derivatives showed various mesophasic phase transitions at relatively low temperatures (in some cases, about 100 °C) due to high conformational freedom and flexibility of alkyl groups . Electronic devices, including PSCs, may exhibit decreased long‐term temporal stability due to low‐temperature mesophasic phase transitions in the ETM.…”
Section: Resultsmentioning
confidence: 99%
“…In previously reported NDI derivatives, introducing N ‐substituted flexible alkyl groups resulted in high solubility in common organic solvents. However, the derivatives showed various mesophasic phase transitions at relatively low temperatures (in some cases, about 100 °C) due to high conformational freedom and flexibility of alkyl groups . Electronic devices, including PSCs, may exhibit decreased long‐term temporal stability due to low‐temperature mesophasic phase transitions in the ETM.…”
Section: Resultsmentioning
confidence: 99%
“…3 can be simplified as: (4) where the final expression of the threshold voltage under illumination, V th,ill , is [35], illumination, which presumably reflects the increase in the deep-level trapped charge density at the gate insulator/organic semiconductor interface [36][37][38]. The deep-level trapped charge density can be determined according to the following equation [26,39]: (6) where C i is the insulator capacitance per unit area and q is the electronic charge. The obtained values of were given in Table 1.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Organic semiconductors (OSCs) are of great interest as active materials for many technology devices due to many fundamental advantages, including lightweight, low-cost processing, large area capability, structural flexibility and low-temperature process [1][2][3]. The efforts in the research and development of OSCs lead to developing industrial electronic and optoelectronic organic devices such as organic light-emitting diodes (LEDs), organic photovoltaic cells (OPVs), organic thin film transistors (OTFTs), organic memories and organic sensors [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Organic semiconductors have gained considerable attention due to their potential applications in organic light-emitting diodes (OLEDs) [1][2][3][4], organic photovoltaics (OPVs) [5][6][7][8] and organic thin film transistors (OTFTs) [9,10]. In fabrication of the organic thin film transistors (OTFTs), conjugated polymers, oligomers, or small molecules are generally used as organic active layer.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, soluble organic semiconductors enable simple processing techniques, such as spin coating and drop-casting [11], and printing processes which are ideally suited to the realization of low-cost, flexible [17]. Among solution processed OSCs, thiophene and pentacene derivatives exhibit good TFT performance [10]. Sheraw et al [18] reported that with a simple modification of 6,13-pentacenequinone, 6,13-bis(triisopropylsilylethynyl)pentacene (TIPS-pentacene) can be synthesized.…”
Section: Introductionmentioning
confidence: 99%